Expert problem solving practice in commercial property valuation: an exploratory study. Issue 4 (2nd July 2018) - Amidu, Abdul-Rasheed; Boyd, David
Abstract : Purpose: The purpose of this paper is to identify the core dimensions of problem solving of experts in commercial valuation in order to provide a rich stimulus for managing current practice and enabling future development. Design/methodology/approach: The study adopted a cognitive position but emphasised understanding the everyday commercial property valuation practice in a naturalistic context and from the participants' perspectives. Given this, a grounded theory approach was employed as a research strategy to guide the data collection and surface theoretical interpretations. Data were obtained through in-depth interviews with practicing valuers working in private real estate firms within metropolitan Birmingham, UK. Findings: The interviews uncover four dimensions of experts' problem-solving practice in commercial valuation: multidimensional, domain-specific knowledge base; cognitive process that is centred on analysis and reflection; collaborative problem-solving venture with colleagues; and professional practice issues awareness. A conceptual model is proposed which integrates these dimensions enabling a clearer understanding of the nature of valuation work. Research limitations/implications: This study was designed to be descriptive and theory generating, thus, the findings cannot be generalised as the sample was confined to one city and consists of a small number of senior practicing valuers. Therefore, the findings may not be fully applicable to other practicing valuers, other geographical locations or more widely to other types of property valuation. Nevertheless, the findings provide an important cognitive framework which can be verified by other researchers seeking to examine the practice of expert valuers. Practical implications: The identification of the core dimensions of expert problem solving in commercial property valuation is shown to have implications for valuation practice, education and continued research. The valuation practice environments need to develop mechanisms to provide time that would enable these multi-dimensions of professional competence to be developed. Further work is needed to expand and refine the model across expert practice in other specialty areas of valuation practice. Originality/value: This study expands the current understanding of valuation process to areas of expertise that have received less coverage in behavioural valuation literature, that is, the central role of knowledge and cognition and how these are integrated for effective valuation problem solving and decision making.